Penyelenggaraan Ketentraman, Ketertiban dan Perlindungan Masyarakat di Tempat Hiburan Persepektif Siyasah Tanfidziyah - Uun Fadhilatul Unsa (Jurnal Hukum Lex Generalis, 2026)
This study is motivated by the gap between normative provisions and the actual implementation of public peace, order, and community protection in entertainment venues. Normatively, the regulation of public peace and order is governed by Law Number 23 of 2014 concerning Regional Government, as well as Regional Regulations on Public Order and Public Peace, which grant authority to local governments to conduct supervision and enforcement. However, empirically (das sein), various violations are still found in entertainment venues, such as disturbances to public order, activities that violate social norms, and weak supervision and law enforcement by authorities. The scientific problem addressed in this study is how the implementation of public peace, order, and community protection in entertainment venues can be analyzed from the perspective of siyasah tanfidziyah, as well as the extent of the gap between legal provisions (das sollen) and their implementation in practice (das sein). This research employs an empirical method with a socio-legal (juridical-sociological) approach, examining both applicable legal provisions and social realities through interviews, observations, and documentation techniques. The results indicate that the implementation of public peace and order in entertainment venues has not been optimal. This is due to weak supervision, lack of awareness among business actors and the community, and suboptimal coordination among related institutions. From the perspective of siyasah tanfidziyah, this condition reflects that the executive function in upholding public welfare has not been effectively carried out. It is necessary to strengthen the role of local governments in enforcing regulations and to enhance public awareness in order to achieve order and protection oriented toward public welfare.